Isolation and speciation of genus candida in patients undergoing chemotherapy and radiotherapy for head and neck tumours - Yogitha, P. V. V.; Lakshmi, N.; Lakshmi, Koripella Rama; Krishna, Perala Bala Murali; Cheemala, Sulakshana Sony (International Journal of Research in Medical Sciences, 2017)
Background: Fungal infections occur as a result of defect in the immune system. The use of wide-spectrum antibiotics, immunosuppressive therapy, HIV and an increasing incidence of diabetes are some of the causes that resulted in raising number of immunocompromised individuals, in the global scenario. Opportunistic fungal infections mainly oral candidiasis is common in patients undergoing chemotherapy (CT) or radiotherapy (RT) for Head & Neck tumors. Objectives: Isolation and speciation of Candida with antifungal susceptibility testing in patients undergoing CT and RT for Head and Neck tumors. Methods: Study group comprised of 100 saliva samples collected by oral rinse method, (50 chemotherapy and 50 radiotherapy) from inpatients of King George hospital, Visakhapatnam and 50 normal healthy individuals were taken as control group. Standard mycological tests for the Candida isolation, speciation and antifungal susceptibility were done. Results: In the study group out of the 100 patients, 38% were culture positive for Candida. The most commonly isolated species was C. albicans (60.5%) followed by non albicans species. Most of the candida species showed sensitivity to nystatin, amphotericin B, itraconazole and Ketoconazole. In control group 9 out of 50 samples (18%) were culture positive and all the isolates were Candida albicans. Conclusion: Increase in frequency of oral candidiasis in patients undergoing chemotherapy and radiotherapy was observed. The increase in positivity may be attributed to inadequate nutritional status and poor oral hygiene during chemotherapy and radiotherapy. Culture positivity is more in RT patients than in CT patients. Though C. albicans is the predominant isolate, non albicans species are also emerging. All the Candida species isolated from study group were sensitive to nystatin, amphotericin B, itraconazole and ketoconazole. In the study group all the Candida species were resistant to clotrimazole and fluconazole and in the control group all the C. albicans were sensitive to fluconazole.